Disclosure of PrEP use by young women in South Africa and Tanzania: qualitative findings from a demonstration project. Issue 2 (1st February 2021) - Scorgie, Fiona; Khoza, Nomhle; Baron, Deborah; Lees, Shelley; Harvey, Sheila; Ramskin, Lethabo; Stangl, Anne; Colombini, Manuela; Mashauri, Emma; Delany-Moretlwe, Sinead; ,
Abstract: Investigating how young women disclose oral pre-exposure prophylaxis (PrEP) use is important given evidence that disclosure is associated with higher adherence. We report qualitative results on PrEP disclosure among young women in South Africa and Tanzania who participated in a PrEP demonstration project (EMPOWER). In total, 81 in-depth interviews were conducted with 39 young women aged 16–24 years—25 from Johannesburg and 14 from Mwanza—at approximately 3, 6 and/or 9 months post-enrolment. Analysis of data was thematic and inductive. Most Johannesburg participants were students in the inner-city; in Mwanza, all worked in recreational venues, occasionally engaging in sexual transactions with customers. A continuum of approaches was evident. Partner disclosure was common in Johannesburg but less so in Mwanza, where many partners were feared as judgemental and potentially violent. In both sites, participants commonly disclosed to family to secure support, and to friends and work colleagues to advocate about PrEP and encourage uptake among at-risk peers. Adherence clubs appeared helpful in building participants' skills and confidence to disclose, particularly in gender-inequitable sexual relationships. PrEP counselling for young women should focus on strengthening communication skills and helping develop strategies for safe disclosure.